Lead and arsenic in bones of birds of prey from Spain - Mateo, R; Taggart, M; Meharg, A A (2003)
The bones (humerus and/or femur) of 229 birds of prey from 11 species were analyzed for Pb and As to evaluate their exposure to Pb shot. The species with the highest mean Pb levels were red kite (Milvus milvus) and Eurasian griffon (Gyps fulvus), and the species with the lowest levels were Eurasian buzzard (Buteo buteo) and booted eagle (Hieraaetus pennatus). Red kite also had the highest mean As level, an element present in small amounts in Pb shot. Elevated bone Pb concentrations (>10 microg/g dry weight) were found in 10 birds from six species. Clinical signs compatible with lethal Pb poisoning and/or excessive bone Pb concentrations (>20 microg/g) were observed in one Eurasian eagle-owl (Bubo bubo), one red kite, and one Eurasian griffon. Pb poisoning has been diagnosed in eight upland raptor species in Spain to date.